Factors associated with violence with adolescents in the school context: an integrative review (Research, Society and Development, 2022)
Since school violence is defined as a multi-causal phenomenon, involving social, economic, cultural, geographical and historical factors, this study aimed to verify the evidence available in the literature on factors associated with school violence involving adolescents. For the synthesis of knowledge, an integrative literature review was used in the databases of Latin American and Caribbean Literature on Health Sciences (Lilacs), Medical Literature Analysis and Retrieval System Online (Medline/PUBMED), Web of Science and Scopus, where a total of 21 articles were collected in the time frame from 2014 to 2018 and submitted to analysis from thematic categories. Eight categories associated with school violence/bullying emerged: 1) the sociodemographic profile of those involved in school violence, 2) the influence of interpersonal relationships, 3) feelings with the school and the school body, 4) the forms of violence perpetrated, 5) the protective factors for school violence, 6) the risk factors for school violence, 7) the main causes of victimization, and 8) the actual consequences of cyberbullying. Adolescents who grow up and develop in environments of extreme social inequality and vulnerability, exposed to situations of violence, tend to learn a conception of normalization of violence, in order to reproduce this behavior in situations of conflict, showing that not only intrinsic factors to the school would be directly linked, but also an interrelation with situations of violence established in the family and/or community context. The main protective measures include the promotion of self-esteem, autonomy and empowerment of adolescents.